Organizational context of hospital information system (HIS) in Malaysian public hospitals - Nor Hazana Abdullah, Nurul Izzatty Ismail, (Opción, 2019)
This study aims to recognize the factors affecting the organizational context of Hospital Information System (HIS) implementation at Total Hospital Information System (THIS), Intermediate Hospital Information System (IHIS) and Basic Hospital Information System (BHIS)’s hospitals. A quantitative approach was employed to meet the research objective. The quantitative result of the ANOVA test shows that the factors affecting THIS implementation were significantly different from those in IHIS, and BHIS’s hospitals. In conclusion, each factor in the organizational context is required to be highlighted because it influences the success of HIS’s implementation.